Programa de prevención antirrábica realizados durante la pasantía en la UMATA en las zonas rurales del Municipio de Tarso, Antioquia (2024)
The work is the report of the internship carried out between the months of December 2022 and January 2023, at the UMATA in the municipality of Tarso, in the southwest of the department of Antioquia. During this period, three activities were developed, basically: an anti-rabies vaccination campaign in the 16 villages of the municipality, 4 euthanasias of 1 canine and 3 felines, and 2 conferences with small livestock farmers, about the importance of implementing good livestock practices in the productions.